2022
DOI: 10.3389/fimmu.2021.797172
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphatic GAD-alum Injection Modulates B Cell Response and Induces Follicular Helper T Cells and PD-1+ CD8+ T Cells in Patients With Recent-Onset Type 1 Diabetes

Abstract: Antigen-specific immunotherapy is an appealing strategy to preserve beta-cell function in type 1 diabetes, although the approach has yet to meet its therapeutic endpoint. Direct administration of autoantigen into lymph nodes has emerged as an alternative administration route that can improve the efficacy of the treatment. In the first open-label clinical trial in humans, injection of aluminum-formulated glutamic acid decarboxylase (GAD-alum) into an inguinal lymph node led to the promising preservation of C-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Although activation of regulatory mechanisms capable of suppressing harmful autoreactive responses is a desired effect of antigen-specific immunotherapies ( 60 ), this hypothesis has been generated from experimental animal models but has not yet been demonstrated in humans so far. Deep phenotyping of major immune cell populations in a previous pilot trial showed that the immunomodulatory effect of GAD-alum injections into the lymph nodes did no induced any effect on Tregs, in line with results from previous studies ( 12 , 61 63 ). Changes induced by the treatment included instead expansion of follicular helper T cells (Tfh), and enhancement of CD8+ T cells with Th2 phenotype in parallel to increased exhausted CD8+T cells ( 61 ).…”
Section: Discussionsupporting
confidence: 86%
“…Although activation of regulatory mechanisms capable of suppressing harmful autoreactive responses is a desired effect of antigen-specific immunotherapies ( 60 ), this hypothesis has been generated from experimental animal models but has not yet been demonstrated in humans so far. Deep phenotyping of major immune cell populations in a previous pilot trial showed that the immunomodulatory effect of GAD-alum injections into the lymph nodes did no induced any effect on Tregs, in line with results from previous studies ( 12 , 61 63 ). Changes induced by the treatment included instead expansion of follicular helper T cells (Tfh), and enhancement of CD8+ T cells with Th2 phenotype in parallel to increased exhausted CD8+T cells ( 61 ).…”
Section: Discussionsupporting
confidence: 86%
“…(GAD-alum) delays the progression of T1D with immunomodulatory effects including increased PD-1+ CD69+ cells in both CD8+ and double negative T cells (109,110). Apart from CTLA-4 and PD-1, the next wave of coinhibitory immune checkpoint receptor targets, including Lag-3, Tim-3, and TIGIT, are drawing increasing attention in clinical application.…”
Section: Btla-hvemmentioning
confidence: 99%
“…Low-molecular-weight dextran sulfate reduces the incidence of diabetes and even reverses diabetes in early-onset diabetic NOD mice, at least partly via increasing PD-1 expression in T cells, reducing interferon-γCD4 and CD8 T cells, and enhancing the number of FoxP3 cells ( 107 , 108 ). Intralymphatic injection of aluminum-formulated glutamic acid decarboxylase (GAD-alum) delays the progression of T1D with immunomodulatory effects including increased PD-1+ CD69+ cells in both CD8+ and double negative T cells ( 109 , 110 ).…”
Section: Potential Clinical Application Of Immune Checkpoint Molecule...mentioning
confidence: 99%
“…Experimental approaches for improving T cell mediated diseases have been considerably developed in the last years. 1 Available treatments for autoimmune diseases are based on immunosuppressant drugs, such as methylprednisolone, azathioprine, hydroxychloroquine and mycophenolate mofetil; however, these therapies may not always have the desired efficiency. 2 The use of these drugs significantly improves the clinical output of illnesses but they are also associated with considerable side effects, such as major risks to infections, gonadal failure and bone marrow depression.…”
Section: Introductionmentioning
confidence: 99%